Pengaruh Pelatihan Simulasi Balut Bidai terhadap Tingkat Kesiapsiagaan Menghadapi Bencana Gempa Bumi di SMA Negeri 1 Kasihan Bantul - Qisthi Sabila; Heri Puspito; Astika Nur Rohmah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Indonesia is a country with a high disaster risk, particularly earthquakes. Schools play a strategic role in enhancing students' preparedness for disasters. This study aims to determine the effect of splint bandage simulation training on earthquake preparedness at SMAN 1 Kasihan Bantul. This quantitative study used a pre-experimental one-group pretest-posttest design. The sample consisted of 90 tenth-grade students selected through purposive sampling. The research instrument was a preparedness questionnaire administered before and after the training, analyzed using the Wilcoxon test. The results showed an increase in preparedness from the